2010
DOI: 10.1242/jeb.048017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fin ray flexural rigidity on the propulsive forces generated by a biorobotic fish pectoral fin

Abstract: SUMMARYA biorobotic pectoral fin was developed and used to study how the flexural rigidities of fin rays within a highly deformable fish fin affect the fin's propulsive forces. The design of the biorobotic fin was based on a detailed analysis of the pectoral fin of the bluegill sunfish (Lepomis macrochirus). The biorobotic fin was made to execute the kinematics used by the biological fin during steady swimming, and to have structural properties that modeled those of the biological fin. This resulted in an engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 42 publications
6
109
0
Order By: Relevance
“…Fish fins undergo considerable deformation during movement [14] and this deformation is under partial active control and is a key factor in allowing thrust generation throughout the fin or tail beat cycle [45,46]. The approach of comparing the [13,28] with highvorticity regions used to produce hypothetical vortex ring structure circled in white.…”
Section: Discussionmentioning
confidence: 99%
“…Fish fins undergo considerable deformation during movement [14] and this deformation is under partial active control and is a key factor in allowing thrust generation throughout the fin or tail beat cycle [45,46]. The approach of comparing the [13,28] with highvorticity regions used to produce hypothetical vortex ring structure circled in white.…”
Section: Discussionmentioning
confidence: 99%
“…This design process was similar to that used for the robotic pectoral fin by developed in Tangorra et al Tangorra et al, 2010). The robotic caudal fin model was scaled to have linear dimensions approximately four times larger than an adult bluegill sunfish of 20cm total length.…”
Section: Design Of the Caudal Fin Robotmentioning
confidence: 99%
“…This range encompassed both very stiff (2000ϫ) and very compliant (150ϫ) fins. A further discussion of fin ray scaling to match the material properties of manufactured fin rays to those of the bluegill sunfish is given in Tangorra et al (Tangorra et al, 2010). The fin rays were manufactured using fused deposition modeling (Stratasys Inc., Eden Prairie, MN, USA; material: ABS plastic) and stereolithography (3D Systems, Rock Hill, NC, USA; material: Accura 40 UV resin), and were approximately 10cm long, excluding the attachment base (Fig.4).…”
Section: Mechanical Properties Of Fin Raysmentioning
confidence: 99%
“…As many recent studies have reported that fish can actively deform their fins to achieve different types of locomotion, more and more researchers have realized the importance of these flexible propulsion surfaces on enchancing ability of swimming. Such propulsion surfaces include dorsal fins [2][3][4] and pectoral fins [5][6][7] in body and caudal fin (BCF) propulsion and ribbon fins [8][9][10] in median and paired fin (MPF) propulsion. As the most conspicuous appendage of the fish's body, the caudal fin has also been studied extensively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%